A cellulose-based lithium-ion battery separator capable of promoting lithium-ion migration, and a preparation method and application thereof
By introducing fluorine-containing and cyano-containing modifiers on the cellulose molecular chain and carrying out homogeneous grafting reactions, a cellulose-based lithium-ion battery separator that can promote lithium ion migration was prepared, which solved the shortcomings of the existing separator in promoting lithium ion migration, and achieved efficient lithium ion migration and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411489053.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing cellulose-based lithium-ion battery separators have shortcomings in promoting lithium ion migration, resulting in an increase in the migration resistance of lithium ions in the battery and affecting battery performance.
By introducing fluorine-containing and cyano-containing modifiers on the cellulose molecular chain, a homogeneous grafting reaction is carried out to form chemical groups with deliferative ion function. The modified cellulose solution is formed on a polytetrafluoroethylene film to prepare a cellulose-based lithium-ion battery separator that can promote lithium ion migration.
The prepared separator has excellent lithium ion migration effect, with lithium ion migration up to 0.6-0.8, ion conductivity greater than 1.2 mS/cm, electrolyte absorption rate greater than 350%, and good strength and thermal dimensional stability.
Smart Images

Figure CN119381690B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery separators, and in particular to a cellulose-based lithium ion battery separator capable of promoting lithium ion migration, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have become an important cornerstone for promoting the development of industries such as smart devices and electric vehicles. At present, the main components of commercial lithium-ion batteries include positive and negative electrodes, separators, electrolytes, battery shells, etc. In the commonly used standard electrolyte composed of lithium salts and carbonate solvents, lithium ions will be dispersed in the continuous phase of the electrolyte under the action of solvation, providing the basic conditions for the reciprocating migration of lithium ions inside the battery. However, excessive high dielectric constant solvent molecules will coordinate and aggregate around lithium ions under the action of strong ion-dipole bonds, forming a large-diameter lithium ion solvation structure with a high coordination number and desolvation energy barrier, which makes it difficult for lithium ions to desolvate in the battery and the migration resistance increases sharply, limiting the transmission efficiency of lithium ions and seriously affecting battery performance.
[0003] At present, commercial separators are mainly polyolefin separators, whose inert structures do not contain groups that promote lithium ion migration, which is not conducive to the dissociation of lithium ion solvation structures, and have inherent defects such as non-degradability, poor electrolyte wettability and thermal stability. Cellulose has the advantages of wide sources and renewability. The characteristics of multiple hydroxy groups can give cellulose-based lithium-ion battery separators good electrolyte wettability and chemical modifiability (the maximum degree of substitution can reach 3). However, the large amount of hydroxyl groups contained in cellulose itself will produce strong hydrogen bonds between molecules / intramolecules, which will lead to its high crystallinity, which is not conducive to the rapid migration of lithium ions or lithium ion solvation structures within it. In view of the defects of cellulose-based lithium-ion battery separators, it is necessary to provide a cellulose-based lithium-ion battery separator that can promote lithium ion migration. Summary of the invention
[0004] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a cellulose-based lithium-ion battery separator that can promote lithium ion migration.
[0005] Another object of the present invention is to provide a cellulose-based lithium-ion battery separator prepared by the method and capable of promoting lithium ion migration.
[0006] Another object of the present invention is to provide an application of the cellulose-based lithium-ion battery separator capable of promoting lithium ion migration.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a cellulose-based lithium-ion battery separator capable of promoting lithium ion migration comprises the following steps:
[0009] (1) Preparation of cellulose solution
[0010] ①Preparation of alkali-alcohol-urea solvent
[0011] Prepare the following components in percentage by mass: 5-8% lithium hydroxide, 15-20% propanol (solvent promoter), 10-14% urea, and the balance water; then mix and dissolve the components to form an alkali-alcohol-urea solvent;
[0012] ②Dissolution of cellulose raw materials
[0013] The plant fiber raw material is stirred and dissolved in an alkali-alcohol-urea solvent at -3°C to -8°C to obtain a cellulose solution;
[0014] (2) Homogeneous modification of cellulose solution
[0015] Introducing a fluorine-containing modifier and a cyanide-containing modifier into the cellulose solution obtained in step ②, and performing a grafting reaction under constant temperature and stirring at 3±1° C. to obtain a modified cellulose solution;
[0016] (3) Forming of cellulose-based battery separators
[0017] The modified cellulose solution obtained in step (2) is uniformly coated on the flat surface of the polytetrafluoroethylene film, and then placed in an environment of 40 to 60°C for preheating and shaping, and then immersed in water to complete the final shaping of the diaphragm and the removal of non-cellulose components, and finally hot-pressed and dried at 110±5°C to remove moisture, and the cellulose-based diaphragm is peeled off from the surface of the polytetrafluoroethylene film to obtain the cellulose-based lithium ion battery diaphragm that can promote lithium ion migration.
[0018] The plant fiber raw material in step (1) includes one or more of microcrystalline cellulose, dissolving pulp, cotton pulp, bleached coniferous wood pulp and bleached broadleaf wood pulp.
[0019] The cellulose polymerization degree in the plant fiber raw material described in step (1) is preferably 300-500, and the cellulose content is preferably ≥99.5%.
[0020] In step (1), the temperature for dissolving the plant fiber raw material is preferably -6°C.
[0021] The concentration of the cellulose solution in step (1) is 5% to 8% by mass.
[0022] The fluorine-containing modifier described in step (2) includes one or more of trifluoropropionic acid, 2-amino-3,3,3-trifluoropropionic acid and 2-bromo-3,3,3-trifluoropropionic acid methyl ester.
[0023] The cyano group-containing modifier described in step (2) includes one or more of cyanopropionic acid, 3-cyanobutyric acid, 4-cyanonicotinic acid and 5-cyanoisophthalic acid.
[0024] The grafting reaction time in step (2) is preferably 6 to 12 hours.
[0025] In step (2), the degree of substitution of the delithium ion solvating functional group on cellulose is regulated by adjusting the type and amount of the modifier, that is, the amount of the fluorine-containing modifier and the cyanide-containing modifier can be adjusted according to the actual situation; the amount of the fluorine-containing modifier is preferably calculated based on the final concentration of 0.06 to 0.26 mol / L in the reaction system; the amount of the cyanide-containing modifier is preferably calculated based on the final concentration of 0.10 to 0.43 mol / L in the reaction system.
[0026] The degree of substitution of fluorine groups on the modified cellulose in the modified cellulose solution in step (2) is preferably 0.2 to 0.6, and the degree of substitution of cyano groups is preferably 0.5 to 1.0.
[0027] The preheating and shaping time in step (3) is 5 to 10 minutes.
[0028] A cellulose-based lithium-ion battery separator capable of promoting lithium-ion migration is prepared by any of the methods described above.
[0029] The cellulose-based lithium-ion battery separator has an excellent function of promoting lithium ion migration. The lithium ion migration number of the separator is as high as 0.6-0.8 (preferably 0.7-0.8), the ion conductivity is greater than 1.2 mS / cm (preferably greater than 1.7 mS / cm), the electrolyte absorption rate is greater than 350% (preferably greater than 370%), the strength is 30-40 MPa, and the thickness is only 10-15 μm, the porosity is 60-70%, and the thermal dimensional stability is greater than 200°C.
[0030] The application of the cellulose-based lithium-ion battery separator capable of promoting lithium-ion migration in the field of lithium-ion batteries.
[0031] Compared with the prior art, the present invention has the following advantages and effects:
[0032] 1. The present invention uses common plant fibers as raw materials, and based on homogeneous reaction conditions, grafts fluorine-containing or cyanide-containing modifiers onto cellulose molecular chains, introducing a large number of special chemical groups with lithium ion desolvation functions. The resulting diaphragm has excellent lithium ion migration promoting effects and electrochemical properties.
[0033] 2. The cellulose raw material used in the present invention is cheap, green, environmentally friendly, renewable and degradable.
[0034] 3. The homogeneous grafting method adopted in the present invention is simple and efficient, the types of grafted chemical groups and the degree of substitution are controllable, and the strength of the cellulose membrane formed after homogeneous grafting modification is greatly improved compared with the strength of the ungrafted cellulose membrane.
[0035] 4. The present invention can simultaneously introduce fluorine-containing groups and cyanide-containing groups into the cellulose molecular chain. The two electron-withdrawing groups can act synergistically to effectively reduce the desolvation energy barrier of the lithium ion solvation structure, increase the effective content of lithium ions, and further promote the migration efficiency of lithium ions inside the battery.
[0036] 5. The diaphragm preparation method of the present invention is simple, the diaphragm performance is excellent, it has a significant effect on promoting lithium ion migration, has a good effect on improving the performance of lithium ion batteries, and the preparation process meets the requirements of industrial continuous production. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a photograph of the cellulose-based lithium-ion battery separator prepared in Example 1 of the present invention.
[0038] Figure 2 This is a microscopic morphology of the cellulose-based lithium-ion battery separator that can promote lithium ion migration in Example 2 of the present invention.
[0039] Figure 3 Schematic diagram of the reaction mechanism of the fluorine-containing modifier, the cyanide-containing modifier and the cellulose molecules in the present invention (in the figure, n=300-500). DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The raw materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. The experimental methods in the following examples where specific conditions are not specified are usually based on conventional conditions.
[0041] In the present invention, unless otherwise specified, all percentages (%) are mass percentages.
[0042] The cellulose raw materials involved in the examples and comparative examples of the present invention include microcrystalline cellulose, dissolving pulp, cotton pulp, and bleached coniferous wood pulp, all of which are purchased from Guangdong Yingtong Paper Co., Ltd., wherein the cellulose polymerization degree is 300-500, and the cellulose content is preferably ≥99.5%.
[0043] The lithium hydroxide involved in the embodiments and comparative examples of the present invention was purchased from Shanghai Bangcheng Chemical Co., Ltd., with an effective content of not less than 99.9%; propanol and urea were both of analytical grade purity and purchased from Guangdong Ju Sheng Technology Co., Ltd.; the fluorine-containing modifier and the cyanide-containing modifier were both of analytical grade purity and purchased from Shanghai McLean Biochemical Technology Co., Ltd.
[0044] The polytetrafluoroethylene films involved in the examples and comparative examples of the present invention were purchased from Jiangsu Yawei Composite Materials Co., Ltd. (specifications: 0.03 mm×90 mm×200 mm).
[0045] The strength, thickness, porosity, liquid absorption rate and thermal dimensional stability involved in the embodiments of the present invention and the comparative examples were tested according to the standard GB / T36363-2018; the degree of substitution was tested by nuclear magnetic resonance; the ionic conductivity was tested by the blocking electrode method; and the lithium ion migration number was tested by electrochemical alternating current impedance method. The test results were all averaged from three measurements.
[0046] Example 1
[0047] (1) Dissolution of cellulose raw materials
[0048] Using microcrystalline cellulose (cellulose content ≥99.5%) with a degree of polymerization of 300 as the raw material, it was dissolved in an alkali-alcohol-urea solvent (5% lithium hydroxide, 15% propanol, 10% urea, 70% water) at -6°C under continuous stirring to obtain a clear and transparent cellulose solution in which the dissolved cellulose concentration was 5%.
[0049] (2) Homogeneous modification of cellulose solution
[0050] Trifluoropropionic acid and 3-cyanobutyric acid (CAS No.: 108747-49-5) were used as modifiers and introduced into the 5% concentration cellulose solution obtained in step (1) at a final concentration of 0.06 mol / L and 0.10 mol / L in the reaction system, respectively. The grafting reaction was carried out at 3°C with constant temperature stirring for 6 h to obtain a viscous and transparent modified cellulose solution with a fluorine group substitution degree of 0.2 and a cyano group substitution degree of 0.5.
[0051] (3) Forming of cellulose-based battery separators
[0052] The modified cellulose solution obtained in step (2) is evenly coated on the flat surface of the polytetrafluoroethylene film, and then placed in a 40°C environment for 10 minutes for preheating and shaping, and then immersed in deionized water to complete the final shaping of the separator and the removal of non-cellulose components. Finally, the cellulose-based separator on the surface of the polytetrafluoroethylene film is peeled off by hot pressing and drying at 110°C to obtain the cellulose-based lithium ion battery separator that can promote lithium ion migration ( Figure 1 ).
[0053] Example 2
[0054] (1) Dissolution of cellulose raw materials
[0055] Taking dissolving pulp with a degree of polymerization of 350 (cellulose content ≥99.5%) as raw material, it was dissolved in an alkali-alcohol-urea solvent (lithium hydroxide 6%, propanol 18%, urea 12%, water 64%) at -6°C under continuous stirring to obtain a clear and transparent cellulose solution in which the dissolved cellulose concentration was 6%.
[0056] (2) Homogeneous modification of cellulose solution
[0057] 2-Amino-3,3,3-trifluoropropionic acid and 4-cyanonicotinic acid (CAS No.: 827616-51-3) were used as modifiers and introduced into the 6% cellulose solution obtained in step (1) at a final concentration of 0.11 mol / L and 0.26 mol / L in the reaction system, respectively. The grafting reaction was carried out at 3°C with constant temperature stirring for 8 h to obtain a viscous and transparent modified cellulose solution with a fluorine group substitution degree of 0.3 and a cyano group substitution degree of 0.7.
[0058] (3) Forming of cellulose-based battery separators
[0059] The modified cellulose solution obtained in step (2) is evenly coated on the flat surface of the polytetrafluoroethylene film, and then placed in a 50°C environment for 8 minutes for preheating and shaping, and then immersed in deionized water to complete the final shaping of the membrane and the removal of non-cellulose components. Finally, the water is removed by hot pressing and drying at 110°C, and the cellulose-based membrane on the surface of the polytetrafluoroethylene film is peeled off to obtain the cellulose-based lithium ion battery membrane that can promote lithium ion migration ( Figure 2 ).
[0060] Example 3
[0061] (1) Dissolution of cellulose raw materials
[0062] Cotton pulp (cellulose content ≥ 99.5%) with a degree of polymerization of 500 was used as raw material and was dissolved in an alkali-alcohol-urea solvent (8% lithium hydroxide, 20% propanol, 14% urea, 58% water) at -6°C under continuous stirring to obtain a clear and transparent cellulose solution in which the dissolved cellulose concentration was 7%.
[0063] (2) Homogeneous modification of cellulose solution
[0064] Methyl 2-bromo-3,3,3-trifluoropropionate and 5-cyanoisophthalic acid (CAS No.: 23341-13-1) were used as modifiers and introduced into the 7% concentration cellulose solution obtained in step (1) at a final concentration of 0.26 mol / L and 0.43 mol / L in the reaction system, respectively. The grafting reaction was carried out at 3°C with constant temperature stirring for 12 h to obtain a viscous and transparent modified cellulose solution with a fluorine group substitution degree of 0.6 and a cyano group substitution degree of 1.0.
[0065] (3) Forming of cellulose-based battery separators
[0066] The modified cellulose solution obtained in step (2) is evenly coated on the flat surface of the polytetrafluoroethylene film, and then placed in a 60°C environment for 5 minutes for preheating and shaping, and then immersed in deionized water to complete the final shaping of the separator and the removal of non-cellulose components. Finally, the water is removed by hot pressing and drying at 110°C, and the cellulose-based separator on the surface of the polytetrafluoroethylene film is peeled off to obtain the cellulose-based lithium-ion battery separator that can promote lithium ion migration.
[0067] Example 4
[0068] (1) Dissolution of cellulose raw materials
[0069] Bleached coniferous wood pulp (cellulose content ≥99.5%) with a degree of polymerization of 450 was used as raw material and dissolved in an alkali-alcohol-urea solvent (8% lithium hydroxide, 16% propanol, 12% urea, 64% water) at -6°C under continuous stirring to obtain a clear and transparent cellulose solution in which the dissolved cellulose concentration was 8%.
[0070] (2) Homogeneous modification of cellulose solution
[0071] 2-Bromo-3,3,3-trifluoropropionic acid methyl ester, 3-cyanobutyric acid and 5-cyanoisophthalic acid were used as modifiers and introduced into the 8% concentration cellulose solution obtained in step (1) at a final concentration of 0.25 mol / L, 0.25 mol / L and 0.15 mol / L in the reaction system, respectively. The grafting reaction was carried out at 3°C with constant temperature stirring for 10 h to obtain a viscous and transparent modified cellulose solution with a fluorine group substitution degree of 0.5 and a cyano group substitution degree of 0.8.
[0072] (3) Forming of cellulose-based battery separators
[0073] The modified cellulose solution obtained in step (2) is evenly coated on the flat surface of the polytetrafluoroethylene film, and then placed in a 60°C environment for 5 minutes for preheating and shaping, and then immersed in deionized water to complete the final shaping of the separator and the removal of non-cellulose components. Finally, the water is removed by hot pressing and drying at 110°C, and the cellulose-based separator on the surface of the polytetrafluoroethylene film is peeled off to obtain the cellulose-based lithium-ion battery separator that can promote lithium ion migration.
[0074] Comparative Example 1
[0075] This comparative example is a cellulose-based lithium-ion battery separator prepared by introducing only a cyano-containing modifier. The preparation process is the same as that of the above example. The specific preparation process is as follows:
[0076] (1) Dissolution of cellulose raw materials
[0077] Using microcrystalline cellulose (cellulose content ≥99.5%) with a degree of polymerization of 300 as the raw material, it was dissolved in an alkali-alcohol-urea solvent (5% lithium hydroxide, 15% propanol, 10% urea, 70% water) at -6°C under continuous stirring to obtain a clear and transparent cellulose solution in which the dissolved cellulose concentration was 5%.
[0078] (2) Homogeneous modification of cellulose solution
[0079] 3-Cyanobutyric acid was used as a modifier and introduced into the 5% concentration cellulose solution obtained in step (1) at a final concentration of 0.21 mol / L in the reaction system. The grafting reaction was carried out at 3°C with constant temperature stirring for 6 h to obtain a viscous and transparent modified cellulose solution with a cyano substitution degree of 0.7.
[0080] (3) Forming of cellulose-based battery separators
[0081] The modified cellulose solution obtained in step (2) is evenly coated on the flat surface of the polytetrafluoroethylene film, and then placed in a 40°C environment for 10 minutes for preheating and shaping, and then immersed in deionized water to complete the final shaping of the membrane and the removal of non-cellulose components. Finally, the water is removed by hot pressing and drying at 110°C, and the cellulose-based membrane on the surface of the polytetrafluoroethylene film is peeled off to obtain a cellulose-based lithium-ion battery membrane modified by a cyanide-containing modifier.
[0082] Comparative Example 2
[0083] This comparative example is a cellulose-based lithium-ion battery separator prepared only after introducing a fluorine-containing modifier. The preparation process is the same as that of the above example. The specific preparation process is as follows:
[0084] (1) Dissolution of cellulose raw materials
[0085] Taking dissolving pulp with a degree of polymerization of 350 (cellulose content ≥99.5%) as raw material, it was dissolved in an alkali-alcohol-urea solvent (lithium hydroxide 6%, propanol 18%, urea 12%, water 64%) at -6°C under continuous stirring to obtain a clear and transparent cellulose solution in which the dissolved cellulose concentration was 6%.
[0086] (2) Homogeneous modification of cellulose solution
[0087] 2-Amino-3,3,3-trifluoropropionic acid was used as a modifier and introduced into the 6% cellulose solution obtained in step (1) at a final concentration of 0.37 mol / L in the reaction system. The grafting reaction was carried out at a constant temperature of 3°C with stirring for 8 h to obtain a viscous and transparent modified cellulose solution with a fluorine group substitution degree of 1.0.
[0088] (3) Forming of cellulose-based battery separators
[0089] The modified cellulose solution obtained in step (2) is evenly coated on the flat surface of the polytetrafluoroethylene film, and then placed in a 50°C environment for 8 minutes for preheating and shaping, and then immersed in deionized water to complete the final shaping of the membrane and the removal of non-cellulose components. Finally, the water is removed by hot pressing and drying at 110°C, and the cellulose-based membrane on the surface of the polytetrafluoroethylene film is peeled off to obtain a cellulose-based lithium-ion battery membrane modified by a fluorine-containing modifier.
[0090] Comparative Example 3
[0091] This comparative example is a cellulose-based lithium-ion battery separator prepared by introducing only a cyano-containing modifier. The preparation process is the same as that of the above example. The specific preparation process is as follows:
[0092] (1) Dissolution of cellulose raw materials
[0093] Cotton pulp with a degree of polymerization of 500 (cellulose content ≥ 99.5%) was used as raw material and was dissolved in an alkali-alcohol-urea solvent (8% lithium hydroxide, 20% propanol, 14% urea, 58% water) at -6°C under continuous stirring to obtain a clear and transparent cellulose solution in which the dissolved cellulose concentration was 7%.
[0094] (2) Homogeneous modification of cellulose solution
[0095] 5-Cyanoisophthalic acid was used as a modifier and introduced into the 7% concentration cellulose solution obtained in step (1) at a final concentration of 0.69 mol / L in the reaction system. The grafting reaction was carried out at a constant temperature of 3°C with stirring for 12 h to obtain a viscous and transparent modified cellulose solution with a cyano substitution degree of 1.6.
[0096] (3) Forming of cellulose-based battery separators
[0097] The modified cellulose solution obtained in step (2) is evenly coated on the flat surface of the polytetrafluoroethylene film, and then placed in a 60°C environment for 5 minutes for preheating and shaping, and then immersed in deionized water to complete the final shaping of the membrane and the removal of non-cellulose components. Finally, the water is removed by hot pressing and drying at 110°C, and the cellulose-based membrane on the surface of the polytetrafluoroethylene film is peeled off to obtain a cellulose-based lithium-ion battery membrane modified by a cyanide-containing modifier.
[0098] Comparative Example 4
[0099] This comparative example is a cellulose-based lithium-ion battery separator prepared only after introducing a fluorine-containing modifier. The preparation process is the same as that of the above example. The specific preparation process is as follows:
[0100] (1) Dissolution of cellulose raw materials
[0101] Bleached coniferous wood pulp (cellulose content ≥99.5%) with a degree of polymerization of 450 was used as raw material and dissolved in an alkali-alcohol-urea solvent (8% lithium hydroxide, 16% propanol, 12% urea, 64% water) at -6°C under continuous stirring to obtain a clear and transparent cellulose solution in which the dissolved cellulose concentration was 8%.
[0102] (2) Homogeneous modification of cellulose solution
[0103] 2-Bromo-3,3,3-trifluoropropionic acid methyl ester was used as a modifier and introduced into the 8% concentration cellulose solution obtained in step (1) at a final concentration of 0.65 mol / L in the reaction system. The grafting reaction was carried out at 3°C with constant temperature stirring for 10 h to obtain a viscous and transparent modified cellulose solution with a fluorine group substitution degree of 1.3.
[0104] (3) Forming of cellulose-based battery separators
[0105] The modified cellulose solution obtained in step (2) is evenly coated on the flat surface of the polytetrafluoroethylene film, and then placed in a 60°C environment for 5 minutes for preheating and shaping, and then immersed in deionized water to complete the final shaping of the membrane and the removal of non-cellulose components. Finally, the water is removed by hot pressing and drying at 110°C, and the cellulose-based membrane on the surface of the polytetrafluoroethylene film is peeled off to obtain a cellulose-based lithium-ion battery membrane modified by a fluorine-containing modifier.
[0106] Comparative Example 5
[0107] This comparative example is a non-modified cellulose-based lithium-ion battery separator, and the cellulose solution homogeneous modification in the above embodiment is not performed. The rest of the preparation process is the same as that in the above embodiment. The specific preparation process is as follows:
[0108] (1) Dissolution of cellulose raw materials
[0109] Cotton pulp (cellulose content ≥ 99.5%) with a degree of polymerization of 500 was used as raw material and was dissolved in an alkali-alcohol-urea solvent (8% lithium hydroxide, 20% propanol, 14% urea, 58% water) at -6°C under continuous stirring to obtain a clear and transparent cellulose solution in which the dissolved cellulose concentration was 7%.
[0110] (2) Forming of non-modified cellulose-based battery separators
[0111] The cellulose solution obtained in step (1) is evenly coated on the flat surface of the polytetrafluoroethylene film, and then placed in a 60°C environment for 5 minutes for preheating and shaping, and then immersed in deionized water to complete the final shaping of the membrane and the removal of non-cellulose components. Finally, the water is removed by hot pressing and drying at 110°C, and the cellulose-based membrane on the surface of the polytetrafluoroethylene film is peeled off to obtain a non-modified cellulose-based lithium-ion battery membrane.
[0112] Effect Example
[0113] The physical properties and electrochemical properties of various cellulose-based lithium-ion battery separators prepared in Examples 1-4 and Comparative Examples 1-5 were compared; wherein, the ionic conductivity and lithium ion migration number were tested after the above-mentioned battery separators were further assembled into batteries: R2032 was used as the standard test battery. The cut lithium iron phosphate positive electrode sheet (LF0609), the above-prepared battery separator, and the graphite negative electrode sheet (SM0206) were stacked concentrically in sequence, placed in an R2032 battery shell, and 30 μL of lithium-ion battery electrolyte (model LFP01, lithium salt is lithium hexafluorophosphate, dissolved as EC (ethylene carbonate): DMC (dimethyl carbonate) = 1:1 (volume ratio)) was dripped and then pressed and sealed to obtain the lithium-ion battery required for the test. The positive electrode sheet, negative electrode sheet, battery shell, and electrolyte were all purchased from Kelude Technology Co., Ltd. The results are shown in Table 1 below.
[0114] Table 1 Performance test of cellulose-based battery separators in examples and comparative examples
[0115]
[0116] Through the above experiments, it was found that the cellulose-based lithium-ion battery separator that can promote lithium ion migration prepared by the present invention can simultaneously introduce fluorine-containing groups and cyanide-containing groups on the cellulose molecular chain through homogeneous modification. Under the synergistic effect of these two chemical groups with strong negative charge absorption effect, the dissociation of the lithium ion solvation structure in the electrolyte can be promoted, thereby improving the migration efficiency of lithium ions, and ionic cross-linking can be formed with the negative ion groups, thereby improving the strength of the separator. However, comparative experiments show that only grafting fluorine-containing groups or cyanide-containing groups, even at a higher degree of substitution, cannot effectively promote the improvement of the lithium ion migration number, which fully proves the good synergistic effect when fluorine-containing groups and cyanide-containing groups exist at the same time.
[0117] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a cellulose-based lithium-ion battery separator capable of promoting lithium ion migration, characterized in that: The steps include: (1) Preparation of cellulose solution ①Preparation of alkali-alcohol-urea solvent Prepare the following components in percentage by mass: 5-8% lithium hydroxide, 15-20% propanol, 10-14% urea, and the balance water; then mix and dissolve the components to form an alkali-alcohol-urea solvent; ②Dissolution of cellulose raw materials The plant fiber raw material is stirred and dissolved in an alkali-alcohol-urea solvent at -3°C to -8°C to obtain a cellulose solution; (2) Homogeneous modification of cellulose solution Introducing a fluorine-containing modifier and a cyanide-containing modifier into the cellulose solution obtained in step ②, and performing a grafting reaction under constant temperature and stirring at 3±1° C. to obtain a modified cellulose solution; (3) Forming of cellulose-based battery separators The modified cellulose solution obtained in step (2) is uniformly coated on the flat surface of the polytetrafluoroethylene film, and then placed in an environment of 40 to 60°C for preheating and shaping, and then immersed in water to complete the final shaping of the diaphragm and the removal of non-cellulose components, and finally hot-pressed and dried at 110±5°C to remove moisture, and the cellulose-based diaphragm is peeled off from the surface of the polytetrafluoroethylene film to obtain the cellulose-based lithium ion battery diaphragm that can promote lithium ion migration.
2. The method according to claim 1, characterized in that: In the modified cellulose solution described in step (2), the degree of substitution of fluorine groups on the modified cellulose is 0.2-0.6, and the degree of substitution of cyano groups is 0.5-1.
0.
3. The method according to claim 1, characterized in that: The fluorine-containing modifier described in step (2) includes one or more of trifluoropropionic acid, 2-amino-3,3,3-trifluoropropionic acid and 2-bromo-3,3,3-trifluoropropionic acid methyl ester; The cyano group-containing modifier described in step (2) includes one or more of cyanopropionic acid, 3-cyanobutyric acid, 4-cyanonicotinic acid and 5-cyanoisophthalic acid.
4. The method according to claim 1, characterized in that: The amount of the fluorine-containing modifier used in step (2) is calculated based on the final concentration of the fluorine-containing modifier in the reaction system being 0.06 to 0.26 mol / L. The amount of the cyano-containing modifier used in step (2) is calculated based on the final concentration of the cyano-containing modifier in the reaction system being 0.10 to 0.43 mol / L.
5. The method according to claim 1, characterized in that: The plant fiber raw material in step (1) includes one or more of microcrystalline cellulose, dissolving pulp, cotton pulp, bleached coniferous wood pulp and bleached broadleaf wood pulp.
6. The method according to claim 1, characterized in that: The cellulose polymerization degree in the plant fiber raw material described in step (1) is 300-500, and the cellulose content is ≥99.5%.
7. The method according to claim 1, characterized in that: The concentration of the cellulose solution in step (1) is 5% to 8% by mass.
8. The method according to claim 1, characterized in that: In step (1), the temperature of dissolving the plant fiber raw material is -6°C; The grafting reaction time in step (2) is 6 to 12 hours; The preheating and shaping time in step (3) is 5 to 10 minutes.
9. A cellulose-based lithium-ion battery separator capable of promoting lithium-ion migration, characterized in that: It is prepared by the method according to any one of claims 1 to 8.
10. Use of the cellulose-based lithium-ion battery separator capable of promoting lithium-ion migration as claimed in claim 9 in the field of lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of oleophobic hydrophobic / hydrophilic functional self-conversion cellulose coating material
CN103374076A
Polyvinylidene fluoride / cyanoethyl cellulose composite lithium ion battery diaphragm and preparation method thereof
CN107256936A